2020
DOI: 10.1038/s41598-019-57201-4
|View full text |Cite
|
Sign up to set email alerts
|

Quasi-periodic ripples in high latitude electron content, the geomagnetic field, and the solar wind

Abstract: in this study we present evidence for the existence of quasi-periodic ripples in the f-region electron content at high latitude, the magnetic flux density at geosynchronous orbit, and the solar wind dynamic pressure and IMF flux density at L1. The ripples are shown to be continually present during all 14 days of observations in different years and seasons, and at all local times, though they are generally small in magnitude relative to the background. The frequencies of all the parameters are, on average, rema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…At nominal solar wind speeds, the PDSs correspond to structures with size scales of the order of the Earth's magnetosphere (Kepko et al., 2020 ). The resultant directly driven ULF waves, observed in the magnetosphere and at the ground, occur at similar frequencies falling within and extending beyond the Pc5 band (Birch & Hargreaves, 2020 ; Hartinger et al., 2014 ; Kepko et al., 2002 ; Kepko & Spence, 2003 ; Stephenson & Walker, 2002 ; Viall et al., 2009 ; Villante et al., 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…At nominal solar wind speeds, the PDSs correspond to structures with size scales of the order of the Earth's magnetosphere (Kepko et al., 2020 ). The resultant directly driven ULF waves, observed in the magnetosphere and at the ground, occur at similar frequencies falling within and extending beyond the Pc5 band (Birch & Hargreaves, 2020 ; Hartinger et al., 2014 ; Kepko et al., 2002 ; Kepko & Spence, 2003 ; Stephenson & Walker, 2002 ; Viall et al., 2009 ; Villante et al., 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…The periodic changes in TEC over high latitude are expected due to the particle precipitation during geomagnetically disturbed conditions (Sato et al 2018;Chernyshov et al 2020). Recently, Birch and Hargreaves (2020) reported that the quasi-periodic oscillations of 25-27 min in the F-region electron content at high latitude, the magnetic field at geosynchronous orbit are caused by the solar wind pressure and IMF. Using the Coupled Magnetosphere-Ionosphere-Thermosphere Model (CITM), Liu et al (2018) and Zhang et al (2019) showed that the energy flow from the solar wind to MI-system strongly depends on the temporal changes in IMF Bz and it also controls the Joule heating, cross polar cap potential, auroral peak electron flux, the vertical plasma drift, and ionospheric F2 peak density variations globally.…”
Section: Discussionmentioning
confidence: 98%
“…These periodic solar-wind structures were first identified by examining the solar wind at Earth when spacecraft in the magnetosphere indicated that the magnetosphere was undergoing periodic compressions (Kepko et al, 2002); the solar-wind periodic structures are also responsible for periodic variations of the total electron content of the Earth's ionosphere (Birch and Hargreaves, 2020a). Periodic density oscillations are found typically in slow solar wind with periods in the range of 4-140 min, corresponding to radial wavelengths of 8 × 10 4 -3 × 10 6 km (Viall et al, 2008;Kepko et al, 2020), which are in the inertial range of scalesizes.…”
Section: Periodic Density Structuresmentioning
confidence: 99%